Green bond experience in the Nordic countries - Darius Nassiry (Asian Development Bank Institute (ADBI), 2018)
The global green bond market has grown rapidly in recent years, increasing from 3 billion in 2012 to over 100 billion in 2017.1 Given the broad acceptance and strong demand from investors, green bonds have emerged as an important financing solution, raising finance for climate change mitigation and adaptation investments, particularly in developing countries, where the need for such investments is significant. The Nordic region has pioneered the issuance of green bonds. The World Bank and Skandinaviska Enskilda Banken (SEB) developed the green bond concept in 2008 in response to investors' demand for climate-related investments. Since then, Nordic issuers have played a leading role in green bond issuance, particularly for local green finance. This paper summarizes the Nordic experience with green bonds with a focus on local financing structures and highlights key points that may be of value for developing countries, particularly those in Asia and the Pacific, in exploring green bonds as a means to raise finance for climate change mitigation and adaptation investments.
Keywords: F3; G2; 330